Whole-Genome Sequencing of Sinocyclocheilus maitianheensis Reveals Phylogenetic Evolution and Immunological Variances in Various Sinocyclocheilus Fishes - Li, Ruihan; Wang, Xiaoai; Bian, Chao; Gao, Zijian; Zhang, Yuanwei; Jiang, Wansheng; Wang, Mo; You, Xinxin; Cheng, Le; Pan, Xiaofu; Yang, Junxing; Shi, Qiong (Frontiers in Genetics, 2021)
An adult Sinocyclocheilus maitianheensis, a surface-dwelling golden-line barbel fish, was collected from Maitian river (Kunming City, Yunnan Province, China) for whole-genome sequencing, assembly, and annotation. We obtained a genome assembly of 1.7 Gb with a scaffold N50 of 1.4 Mb and a contig N50 of 24.7 kb. A total of 39,977 protein-coding genes were annotated. Based on a comparative phylogenetic analysis of five Sinocyclocheilus species and other five representative vertebrates with published genome sequences, we found that S. maitianheensis is close to Sinocyclocheilus anophthalmus (a cave-restricted species with similar locality). Moreover, the assembled genomes of S. maitianheensis and other four Sinocyclocheilus counterparts were used for a fourfold degenerative third-codon transversion (4dTv) analysis. The recent whole-genome duplication (WGD) event was therefore estimated to occur about 18.1 million years ago. Our results also revealed a decreased tendency of copy number in many important genes related to immunity and apoptosis in cave-restricted Sinocyclocheilus species. In summary, we report the first genome assembly of S. maitianheensis, which provides a valuable genetic resource for comparative studies on cavefish biology, species protection, and practical aquaculture of this potentially economical fish.